MOSES LEADERSHIP IN THE BOOK OF EXODUS: IT’S IMPLEMENTATION IN ORGANIZATIONAL DEVELOPMENT - zai, vinus (FILADELFIA: Jurnal Teologi dan Pendidikan Kristen, 2024)
Leadership is the process of influencing or setting an example so that it can encourage a group to achieve a set goal. Moses was one of the successful leaders in the book of Exodus, and his leadership can serve as an example for today's leaders. Organizational coaching is directing a group of people to carry out tasks that have been given in order to achieve a common goal. So, leadership is an important thing in life, leadership has a wide place to influence the way people look, and how they behave. Leadership is the process of influencing or setting an example so that through the process it encourages a group to achieve a set goal (Richard 2005. 33). If a leader is skilled in influencing, it means that the leader has a great opportunity to convey what he wants to his followers, but that influence should be based on the absolute truth values of God. based on the leadership of Moses in the Book of Exodus, an organizational leader must: 1) Must be centered on God, 2) There must be Delegation, 3) No compromise with Sin. To realize the above three thing’s need serious guidance to the group of organizations to achieve the goals to be achieved.